KOMUNIKASI INTERPERSONAL GURU DALAM PROSES PEMBELAJARAN PERILAKU SISWA AUTIS DI SLB PELITA NUSA PEKANBARU - Dita Muslika; Ringgao Eldapi Yozani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Autistic children are understanding that are only interested in their world. Autism is also a condition in which children do what they want, both in thinking and behaving. This situation usually occurs from the age of 2-3 years. where usually children at this age have started to learn to speak, but autistic children experience delays in social interaction, and language problems used. SLB is a school for children with special needs. Interpersonal communication is needed in the learning process between teachers and students with autism. The purpose of this study was to find out how the attitude of openness, empathy, positive attitude, supportive attitude, and equality attitude were carried out by teachers to autistic students at SLB Pelita Nusa Pekanbaru. This study uses a qualitative method with a descriptive approach. This research was conducted at Pelita Nusa Pekanbaru Special School. The selection of informants is done by purposive technique. Data collection techniques consist of observation, interviews, and documentation. While the data analysis technique uses an interactive model by Miles and Huberman. The data validity technique in this study used participation extension and triangulation. The results of this study found that interpersonal communication between teachers and students in the learning process was very effective. The attitude of openness that is carried out is that before communicating the teacher and students must trust each other, the teacher always asks about the news, conditions, and daily lives of students. In empathy, the teacher uses verbal communication, the teacher asks about the condition and pays attention to the student's attitude at that time, while in non-verbal communication the teacher demonstrates body movements to students. The positive attitude of the teacher teaches and provides a good example of greeting and greeting each other. The teacher's supportive attitude provides positive reinforcement and rewards when students succeed in doing something. The attitude of teacher equality does not discriminate but asks according to the needs and abilities of students. Interpersonal communication between teachers and students has a positive impact on autistic students in obtaining education with student deficiencies. Keywords: Interpersonal Communication, Teacher, Autistic Students